2022
DOI: 10.1186/s12913-022-08849-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on HIV service delivery in Miami-Dade County: a mixed methods study

Abstract: Background Facilitating access to HIV prevention and treatment is imperative in Miami-Dade County (MDC), a U.S. HIV epicenter. With COVID-19, disruptions to these services have occurred, leading HIV organizations to innovate and demonstrate resilience. This study documented COVID-19 related disruptions and resilient innovations in HIV services within MDC. Methods This mixed methods cross-sectional study included HIV test counselors in MDC. In the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Despite of considerable heterogeneity of settings and services, 14 out of the 31 included studies (45%) reported decreased testing or reduced lab monitoring during the COVID-19 pandemic resulting in delay in diagnosis. 15 , 22 , 25 , 26 , 28 , 29 , 33 , 35 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite of considerable heterogeneity of settings and services, 14 out of the 31 included studies (45%) reported decreased testing or reduced lab monitoring during the COVID-19 pandemic resulting in delay in diagnosis. 15 , 22 , 25 , 26 , 28 , 29 , 33 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…The decrease in traditional facility-based clinic appointments were compensated by virtual telemedicine platforms. 9 , 12 , 15 , 18 , 22 , 23 , 25 , 26 , 28 , 37 Sustainable strategies like home delivery of ART medications, 15 , 30 multi-month dispensing of ART for stable PLHIVs, 13 , 22 provision of HIV self-testing to know one’s sero-status 14 , 20 , 33 has been reported. A study conducted by Parikh et al in Indian setting, reported nutritional supplementation and door-to-door ration delivery along with ART.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quest, LabCorp) that may be more conveniently located than health centers [33,34]. Such low-barrier strategies are effective for increasing PrEP engagement [35][36][37] and have been increasingly adopted in the setting of the COVID-19 pandemic [38,39]. Importantly, both content experts and focus group participants indicated that these strategies would work for some but not all clients, and emphasized a need for tailored approaches that offer individual choice-findings that are consistent with the limited literature supporting individualized approaches to improve PrEP engagement among LMSM [31,32].…”
Section: Discussionmentioning
confidence: 99%